Artists as Iconographers - Chabert, Garance; Mole, Aurélien; Aubart, François; Luquet-Gad, Ingrid; Verwoert, Jan; Chaillou, Timothée (S.l. : Empire Books, 2020)
Editors: Garance Chabert & Aurélien Mole Texts: François Aubart, Garance Chabert & Aurélien Mole, Ingrid Luquet-Gad, Jan Verwoert. Interviews: Pierre-Olivier Arnaud, Barbara Breitenfellner, Céline Duval, Haris Epaminonda, Aurélien Froment, Wade Guyton, Camille Henrot, Thomas Hirschhorn, Pierre Leguillon, Jonathan Monk, Clément Rodzielski, Linder Sterling, John Stezaker, Oriol Vilanova, by Timothée Chaillou. 32 pages leaflet, Turmoil, Batia Suter, 2020, layered reproductions excerpt from a series in progress, various size. Courtesy of Batia Suter.
For over a century now, iconographer artists have fuelled their approach by tapping into the diversity of images produced by othersand spread through society by industrial means. From collage to the post-internet school, from archival installations to Appropriationist quotation and image constellations, the present book puts these art practices into perspective, focusing on the last forty years, an extraordinarily dynamic period that recently witnessed the invention and development of a new way of disseminating information and images, the internet. Through theoretical texts, artists’ interviews, and exhibition practices, the book maps the connections artists maintain with images and examines emotion as the driving force in our interactions with them. (provided by publisher)
boek